A systematic review of the immuno-inflammatory dysfunction secondary to viral hemorrhagic fevers; Ebola and Lassa fever. - Samuel Ficenec; Nell Bond; Jerry Zifodya; John Schieffelin (PLoS Neglected Tropical Diseases)
The viral hemorrhagic fevers Ebola and Lassa fever are endemic to Sub-Saharan Africa. Both viruses are characterized by high case fatality risk and lifelong debilitating sequelae including blindness and deafness. However, despite these findings the mechanisms of disease and pathogenesis through which these viruses act remain poorly understood. The objective of this systematic review was to synthesize known data regarding both acute and chronic immune-inflammatory dysfunction. A comprehensive search strategy was conducted from July 2022- August 2024. A total of 1,587 articles were identified and evaluated for inclusion. In total 49 Ebola specific and 31 Lassa fever articles were included in this review. The results of this study found considerable dysregulation in immune-inflammatory homeostasis. Specifically, Ebola was found to induce increased concentrations of molecules associated with immune cell recruitment and migration during acute disease. In addition, the virus led to reduction in innate cell populations and expansion of T-cell population frequencies across disease outcomes. Studies of Lassa fever also demonstrated considerable immune dysregulation. However, given the relative lack of studies the exact mechanism of disease is unclear. Among disease survivors, both viruses demonstrate persistent chronic immune dysregulation years following disease onset. However, associating these findings with post-viral syndromes is controversial.